2023
DOI: 10.1371/journal.pone.0283270
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of overweight and its associated factors among Malaysian adults: Findings from a nationally representative survey

Abstract: The World Health Organization has reported that the prevalence of overweight is a growing problem in many countries, including middle- and lower-income countries like Malaysia. This study aimed to determine the prevalence of overweight and its associated factors among Malaysian adults. A total of 9782 Malaysian adults aged 18 and above were included in this study, representing states and federal territories from the National Health and Morbidity Survey 2019. Sociodemographic data (sex, locality, age, marital s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…BMI is a useful tool to estimate the risk of non-communicable diseases (NCDs) in which a higher BMI was associated with a higher risk for diabetes, hypertension, and hypercholesterolemia. Recently, a study conducted among Malaysians revealed that more than 50% of Malaysians were overweight and increased risks for diabetes by 1.47 fold and 2.6 fold higher risks for hypertension (Chong et al, 2023). Therefore, the Malaysia Ministry of Health (MOH) introduced a new BMI cutoff for Malaysians in which normal BMI had been re-adjusted from 18.5 to 24.9 kg/m 2 in the World Health Organization (WHO) guideline to 18.5 to 22.9 kg/m 2 as reported in the Clinical Practice Guideline (Management of Obesity 2 nd Edition (2023)) considering different body proportion and risk for NCDs among Asians compared to other countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…BMI is a useful tool to estimate the risk of non-communicable diseases (NCDs) in which a higher BMI was associated with a higher risk for diabetes, hypertension, and hypercholesterolemia. Recently, a study conducted among Malaysians revealed that more than 50% of Malaysians were overweight and increased risks for diabetes by 1.47 fold and 2.6 fold higher risks for hypertension (Chong et al, 2023). Therefore, the Malaysia Ministry of Health (MOH) introduced a new BMI cutoff for Malaysians in which normal BMI had been re-adjusted from 18.5 to 24.9 kg/m 2 in the World Health Organization (WHO) guideline to 18.5 to 22.9 kg/m 2 as reported in the Clinical Practice Guideline (Management of Obesity 2 nd Edition (2023)) considering different body proportion and risk for NCDs among Asians compared to other countries.…”
Section: Literature Reviewmentioning
confidence: 99%